The influence of pH value on nitrate and nitrite formation in air-plasma-treated aqueous solutions - ZHANG, Mingjia; LIN, Taiyu; LIU, Guangchao; WU, Binhong; WANG, Xin; CHEN, Qiang (Plasma science & technology, 2025)
A DC air discharge plasma is operated over an aqueous solution of Na 2 SO 4 . Nitrate and nitrite are formed in the solution after the plasma treatment. In order to trace the origin of the nitrate and nitrite, we investigated the processes of the nitrate and nitrite formation as a function of the solution’s pH value. We measured the nitrate with a nitrate ion selective electrode and the nitrite with Griess assay. The results show that air is activated to form nitrogen oxides by discharge plasma, and the dissolution of these nitrogen oxides leads to the formation of nitrate and nitrite. The total nitrogen content of the nitrate and nitrite in the solution is independent, while the nitrate and nitrite production rates are dependent on the solution’s pH value. A high pH environment is beneficial for nitrite formation, while a low pH environment is better for nitrate production. Moreover, the production rates of both nitrate and nitrite are greater in the solution cathode than those in the solution anode.